NILAI KEADILAN SOSIAL PADA MASA PEMERINTAHAN UMAR BIN KHATTAB - M. Dzakwan Makarim; Rizqi Muzaki; Nur Elisa; Nova Rahmadhani; Miftakhul Jannah; Oktavia Safitri; Diya Saha; Dian Rif'iyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the implementation of social justice values during the leadership of Umar bin Khattab, which is often regarded as one of the most exemplary periods in Islamic governance. The problem addressed in this research is how the concept of social justice was applied in political, economic, and social policies under Umar’s administration. The purpose of this study is to analyze the principles, strategies, and impacts of Umar bin Khattab’s leadership in realizing social welfare and equality among the Muslim community. This research employs a qualitative method using a historical approach through literature study, focusing on classical Islamic sources, scholarly books, and relevant academic journals. Data were analyzed descriptively by identifying key policies related to justice, such as the establishment of Baitul Mal, fair distribution of public wealth, supervision of government officials, and protection of the rights of non-Muslims. The results show that Umar bin Khattab consistently upheld social justice through transparent governance, strict accountability, equal legal treatment, and economic reforms that reduced poverty and minimized social inequality. His leadership reflects a strong commitment to public welfare and ethical administration, which remains relevant as a model for modern governance and social development. The study concludes that social justice during Umar’s rule was not merely a moral principle, but a concrete political practice manifested in systemic policies that strengthened societal stability and prosperity